The territorial cooperation policy of EU with third Mediterranean Countries - Yiannis Saratsis; Angelos Kotios (European Regional Science Association (ERSA), 2013)
During the programming period 2007-2013 the Cohesion Policy of EU has adopted and implemented the policy of territorial co-operation between EU Member States but also between EU and third countries. In this framework, the EU co-finances (through the European Regional Development Fund, the pre-accession instrument and the instrument of European neighbourhood policy) a series of cross-border, interregional and transnational co-operation programmes in the Mediterranean Basin. These are programs with economic, political, social and environmental objectives. Specifically, in this area bilateral cross-border co-operation programmes among all EU Mediterranean countries, multinational interregional co-operation programmes (IPA Adriatic, MED ENPI CBC) and transnational co-operation on territorial cohesion of Macro-regions (Programme Med) are implemented. All EU Mediterranean countries and most of the countries of North Africa and Eastern Mediterranean Sea are eligible to the mentioned programmes. The aim of this study is to conduct an interim evaluation of these programs and make suggestions for the new programming period for Cohesion Policy 2014-2020. After the presentation of the theoretical foundation of territorial cooperation we describe the framework and objectives of EU policy of territorial cooperation in the Mediterranean Macro-region as well as the multilateral and transnational cross border cooperation programmes. In a further step we summarize the main achievements and failures of the territorial cooperation programmes in the Mediterranean. We conclude that there are important differences in the path of implementation of the programmes due to many factors like the experience of the partner countries in planning methods and cooperation schemes, the existence (or not) of cooperation structures and clusters, the source of funds (e.g. ERDF, IPA, ENPI, national co-financing), bureaucracy, the culture of cooperation and in some cases political disputes. The evaluation of other aspects like the organization and management of the programmes, the eligibility of expenditure and the approval process of the projects, the monitoring and implementation procedures, the thematic and geographical allocation of the approved projects, highlight many problems that should be solved in the next programming period 2014-2020, in order to improve the effectiveness of the European Territorial cooperation in the Mediterranean Basin and promote economic, social, spatial and environmental cohesion of this macro-region.
Keywords: F55; O22; R19; R58; 330; Europe; Mediterranean Countries; Territorial Cooperation; Policy Evaluation; 5th Programming Period